2011
DOI: 10.1371/journal.pone.0027550
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Grown Sheep Preantral Follicles Yield Oocytes with Normal Nuclear-Epigenetic Maturation

Abstract: BackgroundAssisted reproductive technologies allow to utilize a limited number of fully grown oocytes despite the presence in the ovary of a large pool of meiotically incompetent gametes potentially able to produce live births. In vitro folliculogenesis could be useful to recruit these oocytes by promoting their growth and differentiation.Methodology/Principal Findings In vitro folliculogenesis was performed starting from sheep preantral (PA) follicles to evaluate oocyte nuclear/epigenetic maturation. Chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 61 publications
1
54
1
Order By: Relevance
“…ART-conceived AS patients often possess maternal SNRPN LOM. human, it is important to note that work in other animal models, such as sheep and cattle, support the studies described herein (for example, see Young et al (2001), Suzuki et al (2009), Hori et al (2010, Barboni et al (2011) and Heinzmann et al (2011)). Paramount to assisted reproduction is that timing of ARTs coincides with crucial epigenetic events during gametogenesis and early embryogenesis (Fig.…”
Section: Genomic Imprinting: a Model For Epigenetic Stabilitysupporting
confidence: 72%
“…ART-conceived AS patients often possess maternal SNRPN LOM. human, it is important to note that work in other animal models, such as sheep and cattle, support the studies described herein (for example, see Young et al (2001), Suzuki et al (2009), Hori et al (2010, Barboni et al (2011) and Heinzmann et al (2011)). Paramount to assisted reproduction is that timing of ARTs coincides with crucial epigenetic events during gametogenesis and early embryogenesis (Fig.…”
Section: Genomic Imprinting: a Model For Epigenetic Stabilitysupporting
confidence: 72%
“…These two epigenetic marks are probably realized also thanks to the recruitment of HDAC1, SUV39H1, G9a, HP1, Dnmt1 (Russo et al 2007;Barboni et al 2011), and Dnmt3a (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…The level of DNA methylation then increased before stabilizing in oocytes enclosed in tertiary follicles. The global DNA methylation results already have been analyzed in sheep in vivo-and in vitro-grown oocytes (Russo et al 2007;Barboni et al 2011), but for the first time we have studied this process also in primary follicles and simultaneously with the H3K9me3 signal. Thus, in the present study, we have observed that in sheep female germ cells, H3K9me3 precedes global DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations